English language - Miles, Elaine
Describes how conquests of our island, both military and cultural, have shaped the words that we use. This book takes the reader on a historical journey to the origin of the language.
Includes bibliographical references (p. 127-128) and index.
Keywords: English language -- Phonology, Historical; English language -- History; English language -- Etymology